Pengaruh Model Pembelajaran Daring Terhadap Prestasi Belajara Bahasa Indonesia Siswa Kelas VIII SMP Negeri 1 Bangkinang Seberang Tahun Ajaran 2020/2021 Selama Masa Pandemi Covid 19 - Inia Ertisa; Nazirun; Bambang Irawan (UIR Press, 2022)
This research is motivated by the phenomena that occur in the learning process during the Covid-19 pandemic at SMP Negeri 1 Bangkinang Seberang using a quantitative research design with a descriptive method that aims to describe, analyze, and interpret data systematically so that a real picture of the influence of the model is obtained. online learning on student achievement. The theory used is the theory of Sumatra. Data collection methods used, namely the method of observation and questionnaires. The results of the research on the influence of the online learning model on the learning achievement of class VIII SMP Negeri 1 Bangkinang Seberang Academic Year 2020/2021 are quite influential in the influence of the online learning model on learning achievement in Indonesian. Thus, it can be concluded that the influence of the online learning model on the achievement of learning Indonesian in class VIII SMP Negeri 1 Bangkinang Seberang for the 2020/2021 academic year is 61.6 which is categorized as quite influential.